Nanostrategy for Selective Ethyl Carbamate Removal from Fermented Alcoholic Beverages via Molecular Imprinting Technology - Rosa Perestrelo (Beverages)
Ethyl carbamate (EC), known as urethane, is a naturally occurring potentially carcinogenic metabolite that is widely found in alcoholic beverages and other food-related fermented products. The concern related to the presence of the EC and its toxicity in regularly consumed fermented alcoholic beverages raises global interest in assessing the possible risks to human health. EC mitigation approaches, such as molecular imprinting technology (MIT), have been proposed to target EC while preserving the sensory quality of fermented alcoholic beverages. This review explores the principles of MIT, the advantages and disadvantages of the most common polymerisation approach for molecularly imprinted polymer (MIP) synthesis, the analytical techniques used for MIP characterisation, and the strategies used to mitigate EC in fermented alcoholic beverages, with studies reporting removal efficiencies of up to 84%. Additionally, it highlights the novelty and potential of MIPs, offering practical insights into their integration within the production of fermented alcoholic beverages, highlighting their scalability and cost-effectiveness compared to traditional EC mitigation strategies.